2021
DOI: 10.1371/journal.pntd.0009372
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of Burkholderia pseudomallei in soil in Myanmar

Abstract: Background Burkholderia pseudomallei is a Gram-negative bacterium found in soil and water in many tropical countries. It causes melioidosis, a potentially fatal infection first described in 1911 in Myanmar. Melioidosis is a common cause of sepsis and death in South and South-east Asia, but it is rarely diagnosed in Myanmar. We conducted a nationwide soil study to identify areas where B. pseudomallei is present. Methodology/Principal findings We collected soil samples from 387 locations in all 15 states and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…In a large environmental survey from Thailand, lower levels of organic matter, of phosphorus, potassium, calcium, magnesium, iron and salinity were correlated with the presence of B. pseudomallei in paddy soil samples (Hantrakun et al, 2016). Several additional studies also observed lower iron concentrations (Baker et al, 2015;Manivanh et al, 2017;Swe et al, 2021) and a low content of organic matter associated with B. pseudomallei presence (Baker et al, 2015;Ngamsang et al, 2015;Hantrakun et al, 2016;Manivanh et al, 2017). By comparing soil parameters of paddy field samples in Southern Iran with those of non-paddy soil samples, higher levels of available iron, manganese and organic carbon were detected in paddy soil (Azadi et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In a large environmental survey from Thailand, lower levels of organic matter, of phosphorus, potassium, calcium, magnesium, iron and salinity were correlated with the presence of B. pseudomallei in paddy soil samples (Hantrakun et al, 2016). Several additional studies also observed lower iron concentrations (Baker et al, 2015;Manivanh et al, 2017;Swe et al, 2021) and a low content of organic matter associated with B. pseudomallei presence (Baker et al, 2015;Ngamsang et al, 2015;Hantrakun et al, 2016;Manivanh et al, 2017). By comparing soil parameters of paddy field samples in Southern Iran with those of non-paddy soil samples, higher levels of available iron, manganese and organic carbon were detected in paddy soil (Azadi et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…samples, quantitative bacterial loads were not determined (Baker et al, 2011;Suebrasri et al, 2013;Chandrakar and Dias, 2017;Swe et al, 2021). However, contradictory results were obtained, with some studies reporting higher rates of B. pseudomalleipositive samples during the dry season (Wuthiekanun et al, 1995), whereas others found higher isolation rates during the wet season (Suebrasri et al, 2013;Swe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations